"By Design" and Risk Regulation: Insights from Nanotechnologies. (1st December 2021) - MIETTINEN, Mirella
Abstract : Contemporary risk regulation requires an interdisciplinary approach that integrates science, law and socio-political discourses. This calls for new tools in the risk regulation process that enable regulators to adapt to a constantly changing technological realm and help overcome the interdisciplinarity dilemma. In the field of nanotechnologies, tools proposed in the literature include "by design" approaches. In this article, I analyse how the safe-by-design and benign-by-design concepts, emerging in materials science and drug development, could enhance interdisciplinarity in risk regulation. I suggest that further development and implementation of "by design" from a scientific concept to an adaptive regulatory tool could support progressive risk governance of innovative technological developments and enhance the interdisciplinary approach in risk regulation.